Metadata, communication and understanding in digital marketing communication - Petkova, Teodora (Media and Language, 2022)
The study of digital marketing communications on the Web is inseparable from the study of the ways metadata with which the web content of these communications is or should be described. This article presents the aspects of digital marketing communication and understanding in the interactive, interconnected on the levels of text and metadata, hypermedia environment of the Web. The article argues that the texts of digital marketing communications on the Web should be perceived (and created) both as a collective action and together and from the point of view of their function as digital objects.
Keywords: digital marketing communication; web content; metadata; text